Mental Health: A Study on Post-traumatic Stress Disorder, Anxiety and Depression in Rural and Urban Areas of Southern Angola (Brazilian Journal of Health Research, 2019)
Introduction: Angola is an African country that has lived a civil war for almost 40 years. Much of its population was exposed to war or traumatic events. Stress results from unbalance between demands from aggression situations and resources available to individuals in order to deal with such situations. Individuals facing traumatic events can manifest post-traumatic stress disorder or anxiety and depression reactions. Objective: The aim of the present study is to verify whether there is difference in traumatization, anxiety and depression degree between individuals living in urban (less exposed to war) and rural (more exposed to war) areas. Methods: The sample comprised 300 individuals from Matala (rural area) and other 300 from Lubango community (urban area). Participants were in the age group 18 - 65 years - 22.7% were women and 77.3% were men. Results: Based on the results, there are no significant differences between individuals living the rural and urban areas when it comes to post-traumatic stress disorder. However, higher anxiety levels were observed in rural areas (94.6% versus 76.6% in urban areas), and higher depression prevalence was recorded in urban areas (42% versus 36% in rural areas). Conclusion: Although Angola has been living in peace for approximately 17 years now, its population still presents visible war sequels and markedly high traumatization, anxiety and depression rates.